2020
DOI: 10.26907/esd15.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Literature Reading Classes in Terms of Types of Feedback Provided by EFL Teachers: Does Teaching Experience Play a Determining Role?

Abstract: Reading comprehension is thought to be a very challenging skill for L2 (second language) learners, and definitely the role that feedback has in enhancing reading achievement is undeniable. To shed more light on the issue, this study aimed to investigate the types of feedback utilized by EFL teachers in L2 reading comprehension classes at the intermediate level. The study took a step forward and explored the role of years of teaching experience in the provision of feedback. The study also examined the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…The use of repetition strategy by EFL teachers in reading classes can be seen as a way to increase student engagement and comprehension. This is in line with previous research that has shown the benefits of repetition in language teaching, as it can help learners to better retain information and improve their overall language proficiency (Abdelhalim, 2017;Azizi et al, 2020). However, teachers need to use repetition strategically, as excessive repetition can lead to boredom and disengagement among students.…”
Section: Discussionsupporting
confidence: 88%
“…The use of repetition strategy by EFL teachers in reading classes can be seen as a way to increase student engagement and comprehension. This is in line with previous research that has shown the benefits of repetition in language teaching, as it can help learners to better retain information and improve their overall language proficiency (Abdelhalim, 2017;Azizi et al, 2020). However, teachers need to use repetition strategically, as excessive repetition can lead to boredom and disengagement among students.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, the teachers used conventional methods in this study approaches to teach reading comprehension (e.g., a teacher-centered approach and sitting the students in rows). Azizi et al (2020) argue that refurbishments were the most regularly used form of input in both instructor classes. In addition, both experienced and inexperienced novice teachers tended to use multiple corrective input variations at various distributions.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Although previous studies (Abuseileek & Abualsha'r, 2012;Azizi et al, 2020;García & Martínez, 2018;González, 2010;Jabbari et al, 2017;Joh, 2019;Song & Usaha, 2009;Storch, 2017;Sung, 2021;Waluyo & Rofiah, 2021) have briefly pointed at this issue, no plenary study examined the way synchronous and asynchronous peer feedback types are capable of developing the quality of IELTS candidates' writing. One more gap in the literature which the present study endeavors to cover is related to the effect of synchronous and asynchronous peer feedback on students' use of language function.…”
Section: Introductionmentioning
confidence: 99%